Torture-free cyberspace – a human right. Issue 11 (November 2017) - Newbery, Samantha; Dehghantanha, Ali
Abstract : Definitions of torture range from the emotive to the legal. The media sometimes uses the term in a loose or informal sense – for example, to refer to the pain felt when one's sports team loses a crucial game. 1 This dangerous practice detracts from the severity of torture as defined in law. When international human rights instruments describe the treatment of prisoners as torture, they are referring to severe suffering. News reports also use the term in a non-legal, informal sense to refer to the effects of cyber-bullying. 2 In some instances cyber-bullying can meet the severity-of-suffering aspect of the legal definition of torture, as we will examine.